2019
DOI: 10.1371/journal.pntd.0007555
|View full text |Cite
|
Sign up to set email alerts
|

Large scale detailed mapping of dengue vector breeding sites using street view images

Abstract: Targeted environmental and ecosystem management remain crucial in control of dengue. However, providing detailed environmental information on a large scale to effectively target dengue control efforts remains a challenge. An important piece of such information is the extent of the presence of potential dengue vector breeding sites, which consist primarily of open containers such as ceramic jars, buckets, old tires, and flowerpots. In this paper we present the design and implementation of a pipeline to detect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 54 publications
0
22
0
3
Order By: Relevance
“…The frequency of occurrence and the suitability of containers as breeding sites vary, with ceramic containers generally more suitable than plastic containers. Haddawy et al [ 4 ] detected outdoor open containers which constitute potential dengue vector breeding sites from geotagged Google street view (GSV) images using convolutional neural networks. In this study, we make use of their dataset and provide here a brief description of their approach and their data.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The frequency of occurrence and the suitability of containers as breeding sites vary, with ceramic containers generally more suitable than plastic containers. Haddawy et al [ 4 ] detected outdoor open containers which constitute potential dengue vector breeding sites from geotagged Google street view (GSV) images using convolutional neural networks. In this study, we make use of their dataset and provide here a brief description of their approach and their data.…”
Section: Methodsmentioning
confidence: 99%
“…As noted by Campbell et al [ 37 ], seasonal cycles of dengue disease are observed in every province in Thailand and the public health officials are familiar with the seasonal projections of disease. Besides, we wish to relate the analyses in this study to the results from the previous work [ 4 ] which examined the seasonal correlation between container densities and the Breteau index and found a strong correlation during the dengue season. The distribution of Aedes vectors was found to be influenced seasonally by breeding outdoors rather than indoors in a study in Thailand [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations